(untitled) (Basel Institute on Governance Working Papers, 2025)
Corruption is not simply about individual misconduct. It is a networked phenomenon that arises from entrenched social, economic and political interactions. It is orchestrated through coordination between groups and clusters of individuals. This Working Paper explores the networked nature of corruption and the opportunities this presents for anti-corruption efforts. The aim is to understand how shifting the unit of analysis from individuals to networks helps to understand the persistence and resilience of corruption, while opening up new anti-corruption perspectives. A meta-analysis of findings from more than 15 years of research on informal networks and corruption underpins the conceptualisation of corrupt networks. The paper argues that a focus on networks helps to shed light on the functionality of corruption – from petty bribery to large-scale public procurement fraud – and the underlying social norms that enable it. Understanding the structures, functions and modus operandi of the informal networks associated with corruption and applying the network logic to anti-corruption strategies can help to achieve better outcomes. The paper specifically looks at anti-corruption Collective Action initiatives, suggesting that these should emulate positive aspects of informal networks. About this Working Paper This paper is published as part of the Basel Institute on Governance Working Paper series, ISSN: 2624-9650. You may share or republish it under a Creative Commons BY-NC-ND 4.0 International Licence. The contents are the sole responsibility of the authors and do not necessarily reflect the official position of the Basel Institute on Governance, its donors and partners, or the University of Basel. Suggested citation: Baez Camargo, Claudia, and Jacopo Costa. 2025. ’Understanding the enemy: Insights from corrupt networks to improve anticorruption Collective Action initiatives.’Working Paper 60, Basel Institute on Governance. Available at: baselgovernance.org/publications/wp-60.